A política educacional como viabilizadora de um projeto societário: as proposições da Confederação Nacional da Indústria para o Ensino Médio e a Educação Profissional - Teixeira, Dhaiane de Moraes (2021)
We present in this text the proposals of the National Confederation of Industry – CNI for Brazilian education for the second decade of the 21st century, with emphasis on High School and Professional Education. The analysis of these proposals aims understood as the demands of this bourgeoisi for the education, as well as the role played by this class in the definition of public policies for education in Brazil. Characterized by a qualitative approach, this study is supported by documental and bibliographic analysis. Thus, to compose the empirical source, we used technical documents published by the CNI, namely: Strategic Map of Industry 2013-2022 and Strategic Map of Industry 2018-2022, since the documents translate thinking and actions of the industrial bourgeoisie. In order to support the analysis, we sought theoretical support in the bibliographies to investigate the context of production of Strategic Maps of Industry, seeking to understand the demands of productive restructuring and new developmentalism, as well as understanding the National Confederation of Industry in the national scenario and the role played by the institution in the political scenario, especially in the definition of public policies for educationon. On this way, highlight authors such as Antunes (2000); Deitos (2006); Harvey (2010); Rodrigues (1997) and Melo (2010). The discussion on the subject is shown presently as an important issue for the understanding of Brazilian education, in view of the massive insertion of the private sector in education. Thus, we understand the CNI as one of the social subject that permeate the elaboration of educational policies in the country. We understand that education, despite being a State policy, is the product of sectoral disputes. Thus, the CNI, as representative of the national industry, indirectly aims tension the public education propositions that contribute to the perpetuation of its societal project and that, at times, is manifest in the political guidelines for education.